2018
DOI: 10.1080/17524032.2018.1446037
|View full text |Cite
|
Sign up to set email alerts
|

Between Guilt and Obligation: Debating the Responsibility for Climate Change and Climate Politics in the Media

Abstract: The "common but differentiated responsibility" of developed and developing countries to mitigate climate change is a core principle of international climate politics-but there is disagreement about what this "differentiated responsibility" amounts to. We investigate how newspapers in developed countries (Australia, Germany, United States) and emerging economies (Brazil, India) covered this debate during the UN climate summits in 2004, 2009, and 2014. Newspapers in both types of countries attributed more respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The role of national climate regimes has remained stable in Germany and India, though at different levels: In Germany, the role of national climate politics is comparatively strong (40 percent) whereas in India, it is minimal (six percent). This is in line with Billett's (2010) findings that Indian media coverage on climate change focused mostly on the responsibility of developed countries, and also in line with the results of a comparative analysis of attributions of responsibility based on the same data set as this study (Post et al, 2018). It deviates, however, from a comparative study of climate change coverage by Broadbent et al (2016), who showed that Indian media frame climate change mostly by looking at domestic ecological impacts, whereas German media coverage focuses on climate change's global impact.…”
Section: Patterns Of Legitimation Statementssupporting
confidence: 92%
“…The role of national climate regimes has remained stable in Germany and India, though at different levels: In Germany, the role of national climate politics is comparatively strong (40 percent) whereas in India, it is minimal (six percent). This is in line with Billett's (2010) findings that Indian media coverage on climate change focused mostly on the responsibility of developed countries, and also in line with the results of a comparative analysis of attributions of responsibility based on the same data set as this study (Post et al, 2018). It deviates, however, from a comparative study of climate change coverage by Broadbent et al (2016), who showed that Indian media frame climate change mostly by looking at domestic ecological impacts, whereas German media coverage focuses on climate change's global impact.…”
Section: Patterns Of Legitimation Statementssupporting
confidence: 92%
“…Communication about climate change has become an increasingly investigated subject in contemporary communication science [Post, Kleinen-von Königslöw and Schäfer, 2018;Schmid-Petri et al, 2017;Ziegler, 2017]. On the one hand, empirical studies analyze news coverage on climate change.…”
mentioning
confidence: 99%
“…On the one hand, empirical studies analyze news coverage on climate change. These studies are interested in how causes and consequences of climate change and/or responsibilities and actions to tackle climate change are presented in the news [Hart and Feldman, 2014;Post, Kleinen-von Königslöw and Schäfer, 2018;Schmid-Petri et al, 2017]. On the other hand, studies examine the impact of the exposure to this news coverage on the recipients' knowledge and attitudes about climate change [Kahlor and Rosenthal, 2009;Nisbet, Cooper and Ellithorpe, 2015;Sohlberg, 2017;Ziegler, 2017].…”
mentioning
confidence: 99%
“…The "common but differentiated responsibility" of developed and developing countries to mitigate climate change is the core principle of international climate politics. This principle has evolved from the Kyoto Protocol to the Paris Agreement and the climate governance structure has fundamentally changed [12]. In the mid-2000s, the international community entered into a new period of controversial negotiations of global climate change policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That is, E 1 = E 1 (λ, E 1 , Y 2 ). Using Equations (12) and 15, we derive that the environmental investment function in the developing country is a monotonically decreasing function of λ and Y 2 , but a monotonically increasing function of K 1 . Thus, as the marginal efficiency of capital and the disposable income in the developed country increase, the environmental investment of the developing country will decrease.…”
Section: Region Amentioning
confidence: 99%